Mathematics Education in Rural Communities: An Essay on the Parameters of Respectfol Research - Craig B. Howley (Journal of Research in Rural Education, 2003)
This essay has three parts, each constued as a different parameter of rural eduaction research on mathematics and education: (a) research method, (b) content, and (c) the application of research. The author advises a conservative approach to method, a liberal approach to content, and a radical approach to application. The conservative approach to method accepts the existence of a knowable reality. The liberal approach to content views rural issues broadly and sidesteps deficit models of rural lifeworld. The radical approach to application understands that the use of research finding in the policy realm embeds struggle and contradiction. Discussion concludes which relevant observations about mathematics education.